BUDAYA HUKUM UMKM DAN MASYARAKAT DALAM MENERAPKAN PRINSIP FIRST TO FILE DALAM SISTEM HUKUM MEREK INDONESIA - Al-arisy, Gilang Farhan Ahmad; Rusyda, Muh Farhan Ar; Daffa, Rofi Aisy (Ensiklopedia Sosial Review, 2025)
Abstract: This study examines the legal culture of Indonesian society in implementing the first to file principle within the country's trademark law system. In the context of intellectual property law, the first to file principle grants exclusive rights over a trademark to the first party who officially registers it with the Directorate General of Intellectual Property. However, the implementation of this principle often faces challenges due to the low level of legal awareness among the public regarding the importance of trademark registration. This research aims to analyze the factors that contribute to the weak culture of trademark registration and to evaluate the government's role in building legal awareness in society. This research employs a normative legal method with statutory and conceptual approaches, supported by secondary data including literature, regulations, and policy reports related to trademark protection. The findings indicate that the underdeveloped legal culture, limited access to legal information, and lack of legal education are the main factors hindering the effective implementation of the first to file principle. Although the government has made efforts through public outreach programs, simplified procedures via the e-filing system, and registration incentives, these policies have not yet achieved their intended impact. A more comprehensive and sustainable approach is needed to build a stronger legal culture, including intensified legal education, decentralized access to legal services, and strengthened law enforcement mechanisms. Without a robust legal culture, the first to file principle in Indonesia’s trademark system cannot fully ensure legal certainty and fairness for all stakeholders.Keywords: Legal Culture, Trademark, First To File, Legal Awareness, Legal Protection.